(untitled) (Mustansiria Dental Journal, 2022)
Background: In dentistry, different researchers in various studies have tried various methods and techniques to reuse, recycle and manage the waste of dental materials. CAD/CAM wax could be recycled effectively without any degeneration of its original properties by refreshing with new materials using simple techniques. The objective of the current study is to evaluate the dimensional accuracy of the new modified machinable dental wax for CAD/CAM purposes. Materials and Methods: In the present study three experimental blank discs were performed using the same technique for each type, but with different weight/compositions of dental and mineral waxes. A master die was scanned and designed for the crown copy patterns. Ten identical wax copings were milled for each experimental group (Type I, Type II, and Type III) to compare with the control (Dentify-Germany and Zotion™-China) discs. Wax patterns were cast into metal copies to assess the differences in accuracy values of the axial, proximal, and occlusal surfaces between the wax patterns and metal coping. Result: Non- significant differences were noticed in the thickness accuracy between the wax pattern and the metal copy of the experimental discs of Type (I) and Type (II) that were manually produced compared to the commercial discs (P>0.05). While, Type III showed statistically significant differences were noticed between the wax and metal patterns, at different surfaces except in mesial surface (P<0.05). Conclusion: Wax patterns fabricated using a new version of machinable wax produced by recycling some CAD/CAM wax with different fresh materials showed acceptable dimensional accuracy. Also, it seems to have few significant differences for CAD/CAM purposes in terms of patterns thickness than those obtained available and conventional waxTM.